2019
DOI: 10.1242/jeb.197152
|View full text |Cite
|
Sign up to set email alerts
|

An intra-population heterothermy continuum: notable repeatability of body temperature variation in food-deprived yellow-necked mice

Abstract: Theoretical modelling predicts that the thermoregulatory strategies of endothermic animals range from those represented by thermal generalists to those characteristic for thermal specialists. While the generalists tolerate wide variations in body temperature (T b ), the specialists maintain T b at a more constant level. The model has gained support from inter-specific comparisons relating to species and population levels. However, little is known about consistent among-individual variation within populations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 89 publications
2
5
0
Order By: Relevance
“…In this treatment, heavier individuals may have allocated energy to thermoregulation as well as spermatogenesis, while maintaining mass, similar to what was found in ad libitum fed bats in a food deprivation experiment 26 . Our results correspond to other observations 44 , 45 which showed that torpor use in other small heterothermic mammals decreases with an increase in body mass.…”
Section: Discussionsupporting
confidence: 93%
“…In this treatment, heavier individuals may have allocated energy to thermoregulation as well as spermatogenesis, while maintaining mass, similar to what was found in ad libitum fed bats in a food deprivation experiment 26 . Our results correspond to other observations 44 , 45 which showed that torpor use in other small heterothermic mammals decreases with an increase in body mass.…”
Section: Discussionsupporting
confidence: 93%
“…The fact that the repeatability of a trait is high and significant indicates that the trait maintains its ranking in the population and also suggests that there could be genetic variation associated with it (Boratynski et al 2019 ; Bushuev et al 2010 ). This is also interpreted as a potential to respond to natural selection (i.e., evolutionary potential, see Hayes 2010 ; Mousseau and Roff 1987 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evident adaptive significance of hibernation and daily torpor (hereinafter referred to as the “heterothermic phenotype”), few authors have characterized this phenotype at the intra-population level. This is important, because to respond to natural selection a trait should exhibit: (1) consistent variation (i.e., significant repeatability; Boratynski et al 2019 ; Dohm 2002 ; Hayes et al 1998 ; Labocha et al 2004 ) and (2) fitness consequences (i.e., a significant selection gradient; Arnold 1983 ; Lande and Arnold 1983 ). Several authors have addressed these questions in a range of organisms, populations, and traits in what is known collectively as “phenotypic selection studies” (Kingsolver et al 2001 ; see reviews in Hoekstra et al 2001 ; Kruuk et al 2008 ; Mousseau and Roff 1987 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…"repeatable"; reviewed in Boake 1989;Wolak et al 2012). Over the past two decades, numerous studies have reported moderate to high degrees of repeatability among traits associated with the stress response and whole-animal metabolism (Nespolo & Franco 2007;Rensel & Schoech 2011;Müller et al 2018;Boratyński et al 2019;but see Ouyang et al 2011). While these finding strongly suggest that stress-induced changes in T s and q Tot are also likely to be repeatable in endotherms, the degree of this repeatability remains largely unclear (but see Careau et al 2012).…”
Section: Introductionmentioning
confidence: 99%